Cultivating Virtual Feminist Violence in Alice-Madness Returns and Inferno: Analysis of Video Game Adaptations of Alice in Wonderland and Dante’s Inferno - Khan, Sara (Journal of Research in Humanities, 2023)
The work of media is twofold- one shaping individual perspective of the world and two, synchronizing thoughts with what is being represented through the medium. Although study on the violence inflicted by television has been subjected to research; nevertheless, studies on hyperreal instillation of social reality and stereotyping requires potential insight. The current study keeping in view the cultivation of stereotypes and social identities through hyper-reality i.e. video games, aims at analyzing implicit/explicit representation of feminist violence in the video game adaptations of Alice in Wonderland and Dante’s Inferno. The study employs Hutcheon’s three modes of engagement i.e. ’telling, showing and interactive’ as the theoretical basis to answer five W’s of adaptation. The methodological rubric is built on the Mulvey’s feminist film theory with cultivation theory of violence couched within to develop themes out of the textual/visual content of the two video games i.e. AliceMadness Returns and Inferno. The results of the study reveal the representing, producing and spectating of female characters as violent and subjected to fetishism. Moreover, the depiction in Alice-Madness Returns exposes females perpetrating violence and that of Inferno victim of violence. The study highlighted the gender stereotyping specifically the representation of females subjected to obscenity. Apart from this, the study also contemplated the depiction of violence led various levels in the video games.